Two new species of Elwendia (Apiaceae) from Uzbekistan - Kljuykov, Eugene; Ukrainskaja, Uliana; Lyskov, Dmitry (Phytotaxa, 2018)
Two new species of Apiaceae are described as new to science, Elwendia bucharica from the Hissar Range (Pamir-Alay) and E. ugamica from the Ugom Range (Western Tian-Shan). Both species are related to E. capusii. Elwendia bucharica is distinguished by the short terminal lobes of leaves, number of bracts, shape of pedicels, and number of secretory ducts in petals. Elwendia ugamica is distinguished by the short terminal lobes of stem leaves, terminal umbels of lateral branches, shape of stylopods, and shape of styles.